2004
DOI: 10.1002/da.20017
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine is effective against anxiety and depressive symptoms in long-term treatment of patients with schizophrenia

Abstract: This analysis of data from the open-label extension (OLE) phases of three randomized clinical trials of quetiapine in patients with schizophrenia (n=415) was undertaken to investigate whether the initial improvements in anxiety and depressive symptoms were maintained during long-term treatment. The mean (95% confidence interval [CI]) change from the acute phase baseline in the Factor I score of the Brief Psychiatric Rating Scale (BPRS), which includes somatic concern, anxiety, guilt feelings, and depression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…The mean change of depressive symptoms were 7.8 points on the HAMD-17 total score and 3.4 on the BPRS depressive/anxiety subscale scores with the effect of quetiapine evident from the first week of treatment. These findings are consistent with previous studies reporting the effect of quetiapine on depressive symptoms in patients with acute or chronic schizophrenia (Arvanitis et al, 1997;Khouzam, 2000;Emsley et al, 2003;Kasper, 2004). Emsley et al compared the efficacy of quetiapine with haloperidol for patients with a history of partial response to conventional antipsychotic, and reported that quetiapine produced a greater reduction in depression scores (PANSS depression factor) than haloperidol (À1.6 vs. À0.54) (Emsley et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean change of depressive symptoms were 7.8 points on the HAMD-17 total score and 3.4 on the BPRS depressive/anxiety subscale scores with the effect of quetiapine evident from the first week of treatment. These findings are consistent with previous studies reporting the effect of quetiapine on depressive symptoms in patients with acute or chronic schizophrenia (Arvanitis et al, 1997;Khouzam, 2000;Emsley et al, 2003;Kasper, 2004). Emsley et al compared the efficacy of quetiapine with haloperidol for patients with a history of partial response to conventional antipsychotic, and reported that quetiapine produced a greater reduction in depression scores (PANSS depression factor) than haloperidol (À1.6 vs. À0.54) (Emsley et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…The present study also showed similar findings where HAMD-17 scores were significantly reduced in patients with moderate to severe depression relative to mild depression (t ¼ 4.73, df ¼ 28, p < 0.001). Analysis of data from the open-label extension phases of three randomized clinical trials showed that the mean change in BPRS depression/ anxiety subscale score was À1.13 and À1.33 for acute and long-term phases, respectively (Kasper, 2004). The differences of improvement among studies might be due to the differences in population characteristics (gender, depression severity, and disease stage) or treatment characteristics (dosage differences, dosing schedule).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This property may also be useful for treatment beyond the acute phase. An analysis of data from open-label extension phases of three randomised clinical trials of quetiapine in patients with schizophrenia showed that initial improvements in the symptoms of anxiety during the acute phase were maintained over the longer term (156 weeks) [69].…”
Section: Comparison Of Quetiapine With Other Atypical Antipsychoticsmentioning
confidence: 99%
“…Quetiapine is a broad spectrum antipsychotic that is effective against the symptoms of schizophrenia [1], mania [2,3], and depression [4,5]. It is anxiolytic [6,7] and has antiaggression [8,9] effects. In terms of tolerability, quetiapine has very low propensity to cause extrapyramidal side-effects and hyperprolactinaemia [1], irrespective of dose [10].…”
Section: Introductionmentioning
confidence: 99%